The Ensemble Verification System (EVS): A software tool for verifying ensemble forecasts of hydrometeorological and hydrologic variables at discrete locations - Brown, James D.; Demargne, Julie; Seo, Dong-Jun; Liu, Yuqiong (Environmental modelling & software : with environment data news, 2010)
Ensemble forecasting is widely used in meteorology and, increasingly, in hydrology to quantify and propagate uncertainty. In practice, ensemble forecasts cannot account for every source of uncertainty, and many uncertainties are difficult to quantify accurately. Thus, ensemble forecasts are subject to errors, which may be correlated in space and time and may be systematic. Ensemble verification is necessary to quantify these errors, and to better understand the sources of predictive error and skill in particular modeling situations. The Ensemble Verification System (EVS) is a flexible, user-friendly, software tool that is designed to verify ensemble forecasts of numeric variables, such as temperature, precipitation and streamflow. It can be applied to forecasts from any number of discrete locations, which may be issued with any frequency and lead time. The EVS can also produce and verify forecasts that are aggregated in time, such as daily precipitation totals based on hourly forecasts, and can aggregate verification statistics across several discrete locations. This paper is separated into four parts. It begins with an overview of the EVS and the structure of the Graphical User Interface. The verification metrics available in the EVS are then described. These include metrics that verify the forecast probabilities and metrics that verify the ensemble mean forecast. Several new verification metrics are also presented. Following a description of the Application Programming Interface, the procedure for adding a new metric to the EVS is briefly outlined. Finally, the EVS is illustrated with two examples from the National Weather Service (NWS), one focusing on ensemble forecasts of precipitation from the NWS Ensemble Pre-Processor and one focusing on ensemble forecasts of streamflow from the NWS Ensemble Streamflow Prediction system. The conclusions address future enhancements to, and applications of, the EVS.